(untitled) (Gadau Journal of Pure and Allied Sciences, 2024)
Patent Medicine Vendors (PMVs) are non-pharmacist operated drug-dealers and are the commonest sources of Over-the-Counter (OTC) medications and services in sub-Saharan Africa. PMVs provide primary care and are hinted to play a more critical role in controlling malaria, being the major public health challenge. Inadequate skilled manpower informs the drafting of PMVs into malaria management in various endemic regions. This study examines the relationship between PMVs knowledge, attitudes and practices (KAP) and their personal factors (socio-demographic characteristics, working experiences and previous training experiences). 292 PMV respondents were selected and randomized into intervention and wait-list arms, with 146 respondents in each arm respectively. Simple random sampling and systematic random sampling techniques were used to select the local government councils and subsequently participants from the study district respectively. Baseline data on KAP of respondents with varying ages, gender, educational levels, working experiences and training experiences were analysed using SPSS version 26, to ascertain the influencing factors on KAP. Total response rate was 99.6%, with 100% and 99.3% for intervention and wait-list arms respectively. Knowledge, attitudes and the practices of respondents all showed statistically significant relationships with educational levels (p<0.001). But only knowledge showed significant relationship with attending trainings (p = 0.032). Conversely respondent’s attitudes and their practices showed no statistically significant relationship (p>0.05) with attending trainings and with working experiences. The study gave evidence of the relationships of personal factors with KAP of respondents. Educational levels influenced knowledge, attitudes and practices, while attending trainings influenced only knowledge of respondents.